APPLICATION OF A NOVEL EQUILIBRIUM ANGIOTENSIN II ASSAY IN SCREENING AND CONFIRMATORY TESTING FOR PRIMARY ALDOSTERONISM: A PILOT STUDY. (June 2018) - Guo, Z.; Poglitsch, M.; Mcwhinney, B.; Ungerer, J.; Ahmed, A.H.; Gordon, R.D.; Wolley, M.; Stowasser, M.
Abstract : Objective: Although recommended for screening for primary aldosteronism (PA), many medications and physiological factors affect the aldosterone/renin ratio (ARR). The aldosterone/angiotensin II (AngII) ratio (AA2R), with quantification of AngII using a novel Renin-Angiotensin-System Equilibrium Analysis based on liquid chromatography-tandem mass spectrometry (LC-MS/MS) technology (rather than detection of its upstream regulator renin as used in the ARR), may be less prone to interference. Design and method: Of 68 patients undergoing confirmatory fludrocortisone suppression testing (FST) and demonstrating conclusive results, PA was excluded in 20 and confirmed in 48. Peripheral aldosterone (PAC), equilibrium AngII (eqAngII) and direct renin (DRC) concentrations were measured at 7 AM (recumbent) and 10 AM (upright) basally (day 0) and on day 4 of FST. Results: Basally, PA patients displayed higher (p < 0.01) PAC, ARR and AA2R than non-PA patients, and lower (p < 0.01) DRC and eqAngII. Levels of each were higher (p < 0.01) upright than recumbent. On day 4, upright DRC and eqAngII were suppressed (p < 0.01) in both groups whereas upright PAC in PA patients failed to suppress. DRC and eqAngII displayed positive correlation (correlation coefficient 0.641, p < 0.01) among the 272 blood samples collected; the non-PA group showed stronger correlation (0.840, p < 0.01) than PA (0.479, p < 0.01). DRC was below the lower limit of quantification (LLOQ) in 125 (46.0%) samples versus eqAngII in only 24 (8.8%). Areas under the receiver operation characteristic curve for ARR and AA2R on day 0 were similar (7 AM 0.918 vs 0.927; 10 AM 0.932 vs 0.916). Conclusions: Dynamic changes of DRC and eqAngII show good consistency during FST. EqAngII displays a better performance at low concentrations. The AA2R appears to perform at least as well as ARR and may have the potential for future application in PA screening.